Correlation trend between the bulk modulus, micro hardness and the lattice parameter of III-V semiconductors - Mezouar, Rabie; Bioud, Nadhira; Benmakhlouf, Abdelfateh (International Journal of Advanced Chemistry, 2022)
This work aims to investigate the correlation between the bulk modulus as well as the microhardness and the lattice parameter of several cubic zinc-blende III-V semiconductors. Our study shows that both the bulk modulus and the microhardness correlate no-linearly with the lattice parameter of III-V binary compounds. The best fits were obtained using the Gaussian model, the coefficients of the correlation were found at around 0.993 for the bulk modulus, and 0.996 for the microhardness, respectively. Our expressions perhaps used with high accurate to predict the bulk modulus and the microhardness of other binary compounds and ternary semiconductor alloys.Â Â Â